2019
DOI: 10.5267/j.msl.2019.2.009
|View full text |Cite
|
Sign up to set email alerts
|

Determining intention to buy air e-tickets in Malaysia

Abstract: Struggling airlines can save cost and improve profits by selling tickets online. While global sales of air e-tickets have grown over time, they are mostly from advanced nations. In developing markets like Malaysia, e-ticket sales are substantially lower. Hence, this study sets out to examine the factors that determine consumers' intentions to buy air e-tickets. The factors include the disadvantage and advantage of buying air e-tickets, represented by perceived risk and perceived usefulness, respectively. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
7
0
1
Order By: Relevance
“…In addition, as seen in previous studies (Çelik & Gök Kısa, 2017;Hsu et al, 2012), in the airline industry where services are mainly distributed online, consumers are concerned about the confidentiality of their personal and financial data and, therefore, they pay particular attention to the security criterion. This issue has also been found in past studies as one of the main concerns of passengers during online booking (Bigné et al, 2010;Lee et al, 2019).…”
Section: Resultssupporting
confidence: 62%
“…In addition, as seen in previous studies (Çelik & Gök Kısa, 2017;Hsu et al, 2012), in the airline industry where services are mainly distributed online, consumers are concerned about the confidentiality of their personal and financial data and, therefore, they pay particular attention to the security criterion. This issue has also been found in past studies as one of the main concerns of passengers during online booking (Bigné et al, 2010;Lee et al, 2019).…”
Section: Resultssupporting
confidence: 62%
“…Interestingly, several studies Lee et al, 2019) revealed that e-shoppers are more concerned about online purchase perceived risks than the perceived benefits. Factors such as risk perception of, control over, convenience of the shopping process together with customer service and user friendliness of the shopping website, were demonstrated to be the reasons why some people avoid buying online (Vellido et al, 2000).…”
Section: Online Shopping Behaviour Experiences Motivations Perceivedmentioning
confidence: 99%
“…Results showed that perceived ease of use, awareness, perceived trust, relative advantage, use of e-ticketing, and perceived risk influence online booking of airline tickets. Lee et al's (2019) study developed a structural model to examine the effect of perceived ease of use and perceived usefulness on the intention to purchase air tickets online. Results indicated the significant effect of the two variables.…”
Section: Factors Affecting Consumers' Shoppingmentioning
confidence: 99%